Will fungi solve the carbon dilemma? - Emilia Hannula, S.; Morriën, Elly (Geoderma, 2022)
•We need a better understanding of the distribution of organic matter in soil.•Particulate organic matter (POM) is the best candidate to increase OM content.•Management of agricultural soils could be modified to profit from soil fungi.•Increasing soil fungi will increase soil multifunctionality.•We propose management strategies that steer the structure of the soil food web. Soils are hotspots of diversity and sustain many globally important functions. Here we focus on the most burning issue: how to keep soils as carbon sinks while maintaining their productivity. Evidence shows that life in soils plays a crucial role in improving soil health yet soil ecological processes are often ignored in soil sciences. In this review, we highlight the potential of fungi to increase soil carbon sequestration while maintaining crop yield, functions needed to sustain human population on Earth and at same time keep the Earth livable. We propose management strategies that steer towards more fungal activity but also high functional diversity of fungi which will lead to more stable carbon sources in soil but also affects the structure of the soil food web up to ecosystem level. We list knowledge gaps that limit our ability to steer soil fungal communities such that stabilising carbon in top soils becomes more effective. Using the natural capacity of a biodiverse soil community to sequester carbon delivers double benefit: reduction of atmospheric carbon dioxide by storing photosynthesized carbon in soil and increasing agricultural yields by restoring organic matter content of degraded soils.